Determinants of the adoption of injury risk reduction programmes in athletics (track and field): an online survey of 7715 French athletes. Issue 9 (17th November 2021) - Ruffault, Alexis; Sorg, Marine; Martin, Simon; Hanon, Christine; Jacquet, Lison; Verhagen, Evert; Edouard, Pascal
Abstract : Objectives: To identify individual characteristics associated with the adoption of injury risk reduction programmes (IRRP) and to investigate the variations in sociocognitive determinants (ie, attitudes, subjective norms, perceived behavioural control and intentions) of IRRP adoption in athletics (track and field) athletes. Methods: We conducted a cross-sectional study using an online survey sent to athletes licensed with the French Federation of Athletics to investigate their habits and sociocognitive determinants of IRRP adoption. Sociodemographic characteristics, sports practice and history of previous injuries were also recorded. Logistic regression analyses and group comparisons were performed. Results: The final sample was composed of 7715 athletes. From the multivariable analysis, competing at the highest level was positively associated with IRRP adoption (adjusted OR (AOR)=1.66; 99.9% CI 1.39 to 1.99 and AOR=1.48; 99.9% CI 1.22 to 1.80) and presenting a low number of past injuries was negatively associated with IRRP adoption (AOR=0.48; 99.9% CI 0.35 to 0.65 and AOR=0.61; 99.9% CI 0.44 to 0.84), both during their lifetime and the current season, respectively. These results were supported by higher scores of sociocognitive determinants among athletes who reported IRRP adoption compared with other athletes. Conclusion: Some characteristics of athletes seem to be associated with IRRP adoption either positively (competing at the highest level) or negatively (presenting a lower number of past injuries), whereas all the sociocognitive determinants tested appear to be linked to IRRP adoption. Since many athlete characteristics are difficult or impossible to change, IRRP promotion may be enhanced by targeting athletes' beliefs and intentions to adopt an IRRP.